Rock-fluid interactions in geothermal reservoir systems and the implications for carbon sequestration - Belshaw, Grace (2022)
This thesis aims to examine whether andesitic rock samples are likely to be good targets for permanent carbon sequestration via mineral trapping, as an alternative to basaltic-type reservoirs which have been proven to be successful. The CarbFix project in Iceland and the Wallula Basalt Pilot Scale project both reported results from field scale studies that suggested carbonation reactions had occurred within just two years in basaltic-type reservoirs, which is a significant improvement on the thousands of years needed for other geological carbon storage methods to be considered permanent. Carbon dioxide was successfully sequestered in these systems, after mineral dissolution reactions with the injected acidic fluids, which released divalent cations able to combine with the dissolved CO2 and precipitate carbonate minerals. However, there is a significant lack of research examining whether alternative volcanic rocks such as andesite may also be suitable. If alternative volcanic rocks can also be utilised as targets for permanent carbon sequestration in short timescales, this would expand the accessibility of the CarbFix project to more global locations and help mitigate the impacts of rising CO2 concentrations in the atmosphere.